2017
DOI: 10.2341/16-335-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Curing Modes on Polymerization Behavior and Mechanical Properties of Dual-Cured Provisional Resins

Abstract: This study determined the influence of curing mode on polymerization behavior and mechanical properties of dual-cured provisional resins. Three dual-cured bisacryl-based provisional resins were used: Tempsmart (TS; GC Corp), Luxatemp Automix Solar (LX; DMG Chemisch Pharmazeutishe Fabrik GmbH), and Integrity Multi·Cure (IG; Dentsply Caulk). A self-cured bisacryl-based provisional resin, Protemp Plus (PP; 3M ESPE) and a conventional poly(methyl methacrylate) (PMMA) provisional resin, Unifast III (UF; GC Corp) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 27 publications
1
28
1
Order By: Relevance
“…Most of the provisional resin-based composites showed decreased values with an increased number of TCs. Shibasaki et al investigated the initial polymerization behavior of these DCPRs using ultrasonic measurement, and reported that all of the DCPRs exhibit a lower polymerization rate with self-curing than with dualcuring 12) . Lower polymerization of DCPRs may lead to higher water absorption, resulting in a lower σF during the course of TCs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the provisional resin-based composites showed decreased values with an increased number of TCs. Shibasaki et al investigated the initial polymerization behavior of these DCPRs using ultrasonic measurement, and reported that all of the DCPRs exhibit a lower polymerization rate with self-curing than with dualcuring 12) . Lower polymerization of DCPRs may lead to higher water absorption, resulting in a lower σF during the course of TCs.…”
Section: Discussionmentioning
confidence: 99%
“…The σ F and elastic modulus (E) were determined from the stress-strain curve using computer software (Bluehill version 2.5, Instron) linked to the testing instrument. In addition, the modulus of resilience (R) was calculated using the equation: 12) .…”
Section: Flexural Strength Testmentioning
confidence: 99%
See 3 more Smart Citations